Carcass characteristics of feedlot lambs fed crude glycerin contaminated with high concentrations of crude fat - Lage, J. F. [UNESP]; Paulino, P. V R; Pereira, L. G R; Duarte, M. S.; Filho, S.C. Valadares; Oliveira, A. S.; Souza, N. K P; Lima, J. C M (Elsevier, 2014)
Thirty non-castrated male lambs with 20. ±. 2.3. kg average body weight (BW) were randomly assigned to five treatments consisted of different dietary concentrations of crude glycerin (CG; 0, 3, 6, 9 and 12% on DM basis) to evaluate the effects on performance, carcass and meat quality traits. A quadratic effect was observed for performance (P= 0.04), final BW (P<. 0.01) and hot carcass weight (P<. 0.01). No effects of CG were observed (P>. 0.05) on carcass pH neither on shear-force, cooking loss and ether extract content in longissimus. The inclusion of CG tended to reduce the Zn content in meat (P= 0.09). The data suggests that CG (36.2% of glycerol and 46.5% of crude fat) may be used in diets of finishing lambs with concentrations up to 3% without negative effects on performance and main carcass traits. Moreover, inclusion of CG seems to not affect quality and safety of meat for human consumption. © 2013 Elsevier Ltd.
Keywords: By-product; Feedlot; Glycerol; Ruminants; Sheep; Crude glycerins; Ether extracts; Human consumption; Quadratic effect; Quality and safeties; Byproducts; Mammals; Meats